A Case of Primary Small Cell Carcinoma of the Pancreas Confused with Tumor-Forming Pancreatitis in Dioagnosis - Kawasaki, Takuya; Yanagisawa, Kazuhiko; Iijima, Tatsuo; Ishikawa, Makoto; Koja, Susumu; Ushijima, Ryo; Oda, Tatsuya; Okouchi, Nobuhiro (Nippon Shokaki Geka Gakkai zasshi, 2005)
A 49-year-old man with a history of pancreatitis 3 years previously was referredto our hospital for epigastralgia. Laboratory studies revealed a high serum amylase value of 716IU/l. Abdominal CT showed a low density area (LDA) of 3. 5cm in diameter in the pancreatic head. Magnetic resonance cholangiopancreatography (MRCP) revealed segmental narrowing of the main pancreatic duct (MPD) in thepancreatic head, but no obstruction, and the patient was treated for tumor-forming pancreatitis. Subsequently, laboratory studies revealed high hepato-biliary enzyme value and cholangiopancreatogram showed segmental narrowing, but no obstruction. So, it was unlikely that the diagnosis was conventional pancreatic cancer.But abdominal CT afterwards showed enlargement of the LDA and swelling of several lymph nodes from posterior of the pancreatic head to the para-aortic region. Then, intending to make a definitive diagnosis of possible neoplastic disease, percutaneous fine-needle biopsy was performed 2 months after admission, and the pathological findings showed a small-cell carcinoma pattern. Since CT of the chest showed no clear lesions in the lung, a diagnosis of primary small-cell carcinomaof the pancreas was made. Atypical pancreatic tumors, including small-cell carcinomas, sometimes do not obstruct the pancreatic duct or bile duct, as in this case. We realized the importance of differentiation from tumor-forming pancreatitis, which yields similar findings on cholangiopancreatograms.